A pot of gold at the end of the rainbow: Subsistence cannabis cultivation in the changing legislative context in South Africa - Fortune, Kelly (Department of Public Law, 2022)
Cannabis cultivation is documented as a long-standing practice in Africa and Southern Africa specifically (Paterson 2009, Crampton 2015, Duvall 2019, Khan 2015, United Nations Office on Drugs and Crime 2019). The growing of cannabis is concentrated in three African regions; Pondoland in South Africa, the Mokhotlong district in Lesotho and the Hhohho district in Swaziland, with the majority of farmers growing the crop for subsistence (Crampton 2015:57). Cannabis thus holds significant value in supplementing incomes and sustaining livelihoods, especially of cultivators. Considering their geographic and economic positions, the contribution of cannabis to the livelihoods of those who live in the poorest parts of the country is great, yet has been largely ignored (Kepe 2003:605) despite the changing legislative context of cannabis law in South Africa. Moreover, as changes to the legislative framework emerge and the cannabis legalisation debate deepens, one is challenged in locating the voices of the rural farmers who have cultivated cannabis for generations. As an important source of information, they appear to be left out. What are their views? Are they for or against legalisation and why? What are the perceived impacts of legalisation on their continued production of cannabis? In an attempt to garner and understand their views, needs and concerns, this thesis aims to showcase these, and further open up a small window of opportunity to relay the voices of the seemingly voiceless. It emphasises that, without their voices, a nuanced legalisation debate and support for a holistic, progressive, informed, sustainable legislative framework will be tainted.